Rimbaud, Molière e Sade lidos pelos brasileiros: aspectos da representação literária dos escritores franceses homenageados na coleção Literatura ou Morte - Caron, Elaine Cristina [UNESP] (2015)
Rimbaud, Molière and Sade. These are the three french writers honored, respectively, by Leandro Konder, Rubem Fonseca and Bernardo Carvalho, at the collection Literatura ou morte (2000 published by Companhia das Letras. The idea of the collection would have appeared when Leandro Konder submitted to his publisher the original novel A morte de Rimbaud, in that in addition to quote the french poet in the title, includes references to french literature. Enthusiastic with the result, the publisher Luis Schwarcz contacted several writers to create novels that follow the same model of A morte de Rimbaud, serving two fundamental assumptions: that they were crime novels and involved the name of an established writer by critics and the public, now deceased. Between the seven volumes that followed the proposal are O doente Molière and Medo de Sade. In constructing these novels his authors were brought to revisit the biographies and works of each of the honored writers, providing readings and new meanings to them. The goal of our work is to investigate the reasons Konder, Carvalho and Fonseca to choose the theme of his literary works precisely these three writers, and demonstrated that these choices was not arbitrary, but directed by the publisher, which besides promoting with the reference to the names of classical writers, sets before itself a new group of readers. The collection allows its writers follow two narratives proposals at the same time, it is characterized both as an entertainment literature, marked by the choice of form, crime novel, and biography, and a proposal literature, marked by the theme, which are the classical writers works. These are novels written for both the reader who search a traveling hobby, as to the academic who seeks the references and allusions to other writers. In addition, we aimed to draw a reading that considers the three works together, this perspective that glimpse the formation of a historical-literary...